THEORY AND PRACTICE OF TRANSLATION (Modern education and development, 2025)
This article presents an in-depth exploration of translation as both a theoretical discipline and a practical profession. It analyzes key developments in translation theory, including linguistic, functionalist, cultural, and cognitive perspectives, while also investigating the complex realities of translation practice in various contexts. The study emphasizes the interdependence between theory and practice, arguing that an effective translator must synthesize analytical knowledge with hands-on skills to navigate linguistic, cultural, and technological challenges. The integration of theory into practice and vice versa is not only necessary for academic inquiry but also crucial for professional excellence in today’s globalized communication environment.